Choir of Seeds and Sirens. Indiscipline and Accessible Territories in Guaraní, Quechua, Rarámuri and other Languages - Forns-Broggi, Roberto (2016)
Reflections and thoughts were made about a cinema looking for an activist spectator. She is able to leave her own world behind and cross linguistic and cultural borders. This is a cinema which does not negotiate with neoliberal and mono-linguistic States where heard voices, stories, and tensions in diminished or ignored Amerindian tongues reclaim a dignified existence. This map may be incomplete, but it aims to considerthe contribution of visual anthropology and filmmaking in Latin America by showing some examples of it. It is also a reassessment of Peruvian cinema in which Quechua language is spoken.